2008
DOI: 10.1523/jneurosci.2058-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mesolimbic Functional Magnetic Resonance Imaging Activations during Reward Anticipation Correlate with Reward-Related Ventral Striatal Dopamine Release

Abstract: The dopaminergic mechanisms that control reward-motivated behavior are the subject of intense study, but it is yet unclear how, in humans, neural activity in mesolimbic reward-circuitry and its functional neuroimaging correlates are related to dopamine release. To address this question, we obtained functional magnetic resonance imaging (fMRI) measures of reward-related neural activity and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
360
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(397 citation statements)
references
References 57 publications
(83 reference statements)
36
360
1
Order By: Relevance
“…Moreover, phMRI studies have shown that dopamine releasing agents or agents that block dopamine reuptake increase the BOLD signal in NAc (for review, Knutson and Gibbs, 2007) and that unilateral lesions of dopamine neurons in rat striatum abolished this effect (Chen et al, 1997;Chen et al, 1999;Knutson and Gibbs, 2007). Similarly, a neuroimaging study combining [ 11 C]raclopride positron emission tomography and fMRI showed a strong correlation between BOLD activation during reward anticipation and reward-related dopamine release in the ventral striatum in humans performing a monetary incentive delay task (Schott et al, 2008). Further confirmation of the role of dopaminergic activity in the generation of amperometric O 2 responses in the NAc can be obtained with studies involving coupling of O 2 amperometric responding with pharmacological and/or electrophysiological manipulations.…”
Section: Physiological Origin Of the O 2 Signalmentioning
confidence: 99%
“…Moreover, phMRI studies have shown that dopamine releasing agents or agents that block dopamine reuptake increase the BOLD signal in NAc (for review, Knutson and Gibbs, 2007) and that unilateral lesions of dopamine neurons in rat striatum abolished this effect (Chen et al, 1997;Chen et al, 1999;Knutson and Gibbs, 2007). Similarly, a neuroimaging study combining [ 11 C]raclopride positron emission tomography and fMRI showed a strong correlation between BOLD activation during reward anticipation and reward-related dopamine release in the ventral striatum in humans performing a monetary incentive delay task (Schott et al, 2008). Further confirmation of the role of dopaminergic activity in the generation of amperometric O 2 responses in the NAc can be obtained with studies involving coupling of O 2 amperometric responding with pharmacological and/or electrophysiological manipulations.…”
Section: Physiological Origin Of the O 2 Signalmentioning
confidence: 99%
“…There is ample neuroimaging evidence of the involvement of these areas in tasks that tap the use of rewards to make decisions, especially the ventral striatum (Abler, Walter, Erk, Kammerer, & Spitzer, 2006;Knutson, Taylor, Kaufman, Peterson, & Glover, 2005;Liu, et al, 2011;O'Doherty, Deichmann, Critchley, & Dolan, 2002;Pagnoni, Zink, Montague, & Berns, 2002;Rolls, McCabe, & Redoute, 2008;Schott et al, 2008). In addition, there is recent support for the idea that these areas are functionally connected during reward tasks (Camara, Rodriguez-Fornells, & Munte, 2009;Krebs, Heipertz, Schuetze, & Duzel, 2011;Ye, Hammer, Camara, & Munte, 2011), and rest (Cauda et al, 2011).…”
Section: The Reward Network (Rn)mentioning
confidence: 99%
“…Blood oxygen level-dependent (BOLD) signal increases in VS have been frequently elicited by reward-predictive signals or reward deliveries during functional magnetic resonance imaging (fMRI), and this has been inferred as a marker of phasic dopaminergic activity (Knutson et al, 2001). Notably, individual differences in VS recruitment by reward anticipation (assessed with fMRI) during a monetary incentive delay (MID) task correlated with individual differences in displacement of 11 C raclopride in the VS by MID task rewards themselves (Schott et al, 2008), and with displacement of 18 F fallypride by amphetamine (Buckholtz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%